System Continuance Model for Local E-Government in Indonesia - Herdiana, Dody (2023)
Information and communication technology promises efficiency, speed of information delivery, global reach, and transparency. The development of information and communication technology gave rise to e-government which is a public service model that is carried out online – including in Indonesia. The development of the e-government system in Indonesia has begun to increase in quantity, but the quality is still lacking because the implementation of e-government is not evenly distributed in all regions. In addition, many local e-government projects and local government ongoing use have resulted in significant failure rates. This study aims to determine the level of relevance of the system continuance model in measuring the continuance of local e-government in Indonesia. In addition, this study also aims to find out what factors influence the continuance of local e-government in Indonesia. The research conducted includes quantitative research. The population selected for this research is selected citizens who use local e-government in Indonesia. A total of 390 valid samples were taken and determined based on non-probability sampling using convenience sampling from local e-government users in Indonesia. Valid data were analyzed with SmartPLS 3.0 software using the partial least squares structural equation modelling method with the partial least squares path modelling approach. Variation accounts for 70.2 percent of the total between system use factors and user satisfaction explained by the continuance of the system. The findings from hypothesis testing reveal that nine hypotheses have a significant effect that are supported, except for seven that are not supported, including those that damage the continuance of the system. This finding confirms the importance of quality, meeting citizens' expectations in terms of ease of use and feasibility of e-government support facilities, proven in this study to be the most important factor in the literature on the continuance of e-government systems. This study also provides some fundamental implications for local government agencies. Theoretically, this integrated model can enrich the model for predicting the continuance of e-government systems. Then, in practical terms, this research provides an appropriate approach for stakeholders in government organizations in Indonesia to determine what factors influencing the continuance of local e-government systems need to be considered in order to obtain the highest benefits from e-government projects in Indonesia. Finally, the proposed model shows that it is necessary to improve the quality factors (system quality, service quality, and information quality), behavioural factors (expectation and feasibility).